Perancangan Sistem Informasi Kehadiran Online Pada Fakultas Ilmu Komputer UPN Vetaran Jakarta - Andi Supriyo (2020)
Attendance is something that must be done by students every time they take a course. In doing student attendance at the Faculty of Computer Science, Universitas Pembangunan Nasional Veteran Jakarta still uses paper as an attendance media, even though the UPN Veteran Jakarta campus itself is one of the campuses with a green campus program. Besides this, cheating during absenteeism is still rife because attendance is still manual using paper. Therefore we need a student attendance system that can do data collection and data management so that it can be done quickly and efficiently. Making a web-based student attendance application system design can be done by data collection, system analysis, system design, and system implementation, this online attendance system is made using PHP and MySQL programming languages for database management.